Ancient DNA analyses of early archaeological sites in New Zealand reveal extreme exploitation of moa (Aves: Dinornithiformes) at all life stages - Oskam, C.; Allentoft, M.; Walter, R.; Scofield, R.; Haile, James; Holdaway, R.; Bunce, Michael; Jacomb, C. (Pergamon, 2012)
The human colonisation of New Zealand in the late thirteenth century AD led to catastrophic impacts onthe local biota and is among the most compelling examples of human over-exploitation of native fauna,including megafauna. Nearly half of the species in New Zealand’ s pre-human avifauna are now extinct,including all nine species of large, flightless moa (Aves: Dinornithiformes). The abundance of moa inearly archaeological sites demonstrates the significance of these megaherbivores in the diet of the firstNew Zealanders. Combining moa assemblage data, based on DNA identification of eggshell and bone,with morphological identification of bone (literature and museum catalogued specimens), we presentthe most comprehensive audit of moa to date from several significant 13the15th century AD archaeologicaldeposits across the east coast of the South Island. Mitochondrial DNA (mtDNA) was amplifiedfrom 251 of 323 (78%) eggshell fragments and 22 of 27 (88%) bone samples, and the analyses revealed thepresence of four moa species: Anomalopteryx didiformis; Dinornis robustus; Emeus crassus and Euryapteryxcurtus. The mtDNA, along with polymorphic microsatellite markers, enabled an estimate of the minimumnumber of individual eggs consumed at each site. Remarkably, in one deposit over 50 individual eggswere identified e a number that likely represents a considerable proportion of the total reproductiveoutput of moa in the area and emphasises that human predation of all life stages of moa was intense.Molecular sexing was conducted on bones (n ¼ 11). Contrary to previous ancient DNA studies fromnatural sites that consistently report an excess of female moa, we observed an excess of males (2.7:1),suggestive that males were preferential targets. This could be related to different behaviour between thetwo highly size-dimorphic sexes in moa. Lastly, we investigated the moa species from recovered skeletaland eggshell remains from seven Wairau Bar burials, and identified the presence of only the largerspecies of moa, E. curtus and D. robustus.